1998
DOI: 10.1007/s005340050051
|View full text |Cite
|
Sign up to set email alerts
|

Experience with three-port laparoscopic cholecystectomy

Abstract: After considerable experience with laparoscopic cholecystectomy (LC) using four ports, we began using three-port LC in October 1993 and have performed 130 LCs with this procedure up to May 1996. The procedure was successful in 119 patients. In 6 patients fourth port was used, and in another 5, the procedure was converted to open laparo-tomy. Cooperative manipulation of the surgical instruments between the operator and assistant is very important for this procedure, for exposing Calot's triangle and dissecting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
31
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 7 publications
(9 reference statements)
2
31
0
Order By: Relevance
“…Previous studies have shown that laparoscopic cholecystectomy using only three ports is a safe method. [21][22] Similar findings have been found in this study. This study has shown that there is no significant difference between the operating time between the 3-ports technique and 4-ports technique.The previous studies have shown many factors causing prolonged operative time in laparoscopic cholecystectomy like age, sex, BMI, ASA score, previous abdominal surgery, preoperative endoscopic retrograde cholangiopancreatography, acute cholecystitis, and surgeon's experience.…”
supporting
confidence: 90%
“…Previous studies have shown that laparoscopic cholecystectomy using only three ports is a safe method. [21][22] Similar findings have been found in this study. This study has shown that there is no significant difference between the operating time between the 3-ports technique and 4-ports technique.The previous studies have shown many factors causing prolonged operative time in laparoscopic cholecystectomy like age, sex, BMI, ASA score, previous abdominal surgery, preoperative endoscopic retrograde cholangiopancreatography, acute cholecystitis, and surgeon's experience.…”
supporting
confidence: 90%
“…Several descriptive nonrandomized series have advocated either downsizing the trocars [9,10,11,13,15,17,18,21,22] or reducing the number of trocars [16,20]. Six randomized controlled trials have examined the eects of reducing the size [5,7,12,14,19] or number [6] of laparoscopic trocars in patients undergoing cholecystectomy.…”
mentioning
confidence: 98%
“…In recent years, attempts have been made to minimize the invasiveness, by reducing the size and/or the number of the operating ports and instruments, and even more, the use of a natural orifice as the access port (Natural Orifice Transluminal Endoscopic Surgery-NOTES) [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21].…”
mentioning
confidence: 99%